Social networks and maintenance of an endangered language : the Kejaman of Malaysia - Amee, Joan; Su Hie, Ting (Emerald Publishing Limited, 2025)
Purpose – This study examined how social network influences maintenance of the indigenous language of the Kejaman, a small indigenous group living in Sarawak, Malaysia. Design/methodology/approach – The participants were 123 Kejaman speakersfrom three generationsliving in two longhouses in Belaga, Sarawak. Participants were presented with 20 situations relevant to the lives of Kejaman people to find out the people they interact with. Findings – The grandparents, parents and children’s generations all had more exchange networks (M 5 131.7) than interactive networks (M 5 110.3). They consulted kin on matters related to family, money, culture, death and taboos, providing the avenue for the use of the Kejaman language. Generation 2 had more interactive networks and Generation 3 consulted non-kin on more matters, and the communication takes place in languages other than Kejaman. Chi-Square tests of independence showed no significant differences in the number of exchange and interactive networks across generations. The three generations were not significantly different in uniplexity (M 5 29.5%) and multiplexity scores (M 5 20.6%). The Kejamans belong to a low-density, uniplex social network community. Research limitations/implications – There is a limitation in using social network analysis as a reliable predictor of future language use. This is because social networks are not fixed. They can expand, shrink and change over lifetime, and the fact that the generation of children does not talk about family matters in their mother tongue does not mean that they will not do so in future. Practical implications – Asinteractive networks comprise non-Kejaman people, there will be inadequate close ethnic ties to support transmission and maintenance of Kejaman linguistic and cultural norms. Therefore, their language fluency may decline to the extent that they experience language anxiety and feel uncomfortable using it. Social implications – The quantity and quality of interactive networks for the Kejaman are not conducive for upward mobility. What this meansin the sociopolitical context of Sarawak isthat, thissmall indigenous group is still family-centred and does not have adequate social contacts in the wider society, indicating lack of social standing. Originality/value – The study suggeststhat in future the Kejaman willrely on interactive networksto talk about life-choices, and the lessened contact with Kejaman people will affect maintenance of Kejaman linguistic and cultural norms.